Explicit Solution of Telegraph Equation Based on Reproducing Kernel Method - İnç, Mustafa; Akgul, Ali; Kilicman, Adem (Hindawi Ltd, 2012)
We propose a reproducing kernel method for solving the telegraph equation with initial conditions based on the reproducing kernel theory. The exact solution is represented in the form of series, and some numerical examples have been studied in order to demonstrate the validity and applicability of the technique. The method shows that the implement seems easy and produces accurate results.
Keywords: Boundary-Value-Problems; Efficient Computational Method; Numerical-Solution; Difference Scheme; Heat-Equation; Algorithm; Approximation; System